1992
DOI: 10.1104/pp.100.4.1846
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Regulation of Cytochrome and Alternative Pathway Respiration in Tobacco

Abstract: In suspension cells of NT1 tobacco (Nicotiana tabacum L. cv bright yellow), inhibition of the cytochrome pathway of respiration with antimycin A induced a large increase in the capacity of the alternative pathway over a period of approximately 12 h, as confirmed in both whole cells and isolated mitochondria. The increase in alternative pathway capacity required de novo RNA Mitochondrial electron transport in plants may proceed through either the CP2 or the AP (6,12,14). Transfer of electrons from NADH throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 25 publications
6
66
2
Order By: Relevance
“…The differences between our preliminary results and expectations based upon the published results of Vanlerberghe and Mclntosh (1992) could reflect differences in the types of cultures, organs and organisms tested. Alternatively, mutant mitochondria that have not assembled a functional cytochrome oxidase complex may have different responses from normal mitochondda that have been subjected to chemical inhibition.…”
Section: Discussioncontrasting
confidence: 90%
“…The differences between our preliminary results and expectations based upon the published results of Vanlerberghe and Mclntosh (1992) could reflect differences in the types of cultures, organs and organisms tested. Alternatively, mutant mitochondria that have not assembled a functional cytochrome oxidase complex may have different responses from normal mitochondda that have been subjected to chemical inhibition.…”
Section: Discussioncontrasting
confidence: 90%
“…It has been reported that AOX gene transcription is induced in plant cells by various stimuli, like low temperature (Ito et al 1997), or by natural chemicals such as hydrogen peroxide, salicylate, citrate and cysteine (Vanlerberghe and McIntosh 1996). In P. anomala (Sakajo et al 1991), M. grisea (Yukioka et al 1998), tobacco (Vanlerberghe and McIntosh 1992) and Arabidopsis thaliana , accumulation of AOX mRNA was also observed when the cyanide-sensitive pathway was blocked by inhibitors interacting with complex III. We found that the amount of AOX1 transcripts is increased in a complex III mutant of C. reinhardtii, which indicates that here also the absence of complex III activity determines an overexpression of the gene.…”
Section: Discussionmentioning
confidence: 99%
“…The residual respiration was measured in the assay buffer containing 1 mM KCN and 5 mM SHAM. The capacity of the AOX pathway (V alt ) was calculated as the difference between the cyanide-resistant oxygen uptake and the residual respiration (Bingham & Farrar 1989;Vanlerberghe & McIntosh 1992). The concentrations of both inhibitors used here have been suggested by previous work (Furuhashi et al 1989).…”
Section: Respiration Of Leavesmentioning
confidence: 99%